Antidiabetic Potential of Bryophyllum pinnatum: A Study on its Pharmacological Effects and Synergistic Action with Glibenclamide - Shruti Jaswal; Rajneesh Kaur; Brij Bhusha; Amandeep Kaur; Sarbjot Singh; Anita Devi; Anuneet Kaur; Ankur Thakur (International Journal of Biochemistry and Biomolecule Research, 2025)
Diabetes is a long-term metabolic disorder that profoundly impacts an individual’s overall health, social interactions, and quality of life. While significant progress has been made in diabetes management with the use of medications such as insulin and oral hypoglycemic agents, the limitations of these existing treatments highlight the need for new therapeutic alternatives. Moreover, the high cost of current diabetes medications makes them inaccessible to many, particularly in rural areas of developing countries This study investigates the antidiabetic effects of an aqueous extract of Bryophyllum pinnatum leaves using diabetic albino rats as experimental models. The effectiveness of the extract was compared to a treatment involving both the extract and the conventional antidiabetic drug, glibenclamide. The rats were administered a specific dose of the aqueous extract, and their blood glucose levels (BGL) were monitored throughout the experiment. The results revealed a significant reduction in BGLs, approaching normal levels within 120 minutes when the aqueous extract was used alone. Additionally, when the aqueous extract was combined with glibenclamide, a more pronounced decrease in blood glucose levels was observed. The results of this study indicate that the aqueous extract of Bryophyllum pinnatum leaves exhibits potent antidiabetic properties. Furthermore, the use of this extract appears to enhance the efficacy of the conventional antidiabetic drug, glibenclamide. The plant has many natural chemicals that can affect the body, such as alkaloids, flavonoids, triterpenes, fats, sugars, phenols, bufadienolides, and organic acids. These chemical constituents contribute to the plant’s wide range of pharmacological effects, such as neuropharmacological, nephroprotective, antioxidant, analgesic, antidiabetic, antimicrobial, anticonvulsant, and antipyretic activities. This review explores the various pharmacological effects of Bryophyllum pinnatum.
Keywords: Bryophyllum pinnatum; Diabetes; glibenclamide; hypoglycaemic; hypoglycemic agents; insulin